Filtering via simulation: auxiliary particle filters - Pitt, M; Shephard, N (American Statistical Association, 1999)
This article analyses the recently suggested particle approach to filtering time series. We suggest that the algorithm is not robust to outliers for two reasons: the design of the simulators and the use of the discrete support to represent the sequentially updating prior distribution. Here we tackle the first of these problems.